Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TS-TS) Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 4 Tarutung Tahun Pembelajaran 2023/2024 - Panggabean, Lima Udur; Napitupulu, Tianggur M; Telaumbanua, Eben H; Hulu, Adiani; Nababan, Damayanti (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
The purpose of this study is to determine the positive and significant influence of the use of the Two Stay Two Stray (TS-TS) type cooperative learning model on the learning activity of PAK students of grade VIII SMP Negeri 4 Tarutung Learning Year 2023/2024. The research method used is quantitative research method. The population is all grade VIII students of SMP Negeri 4 Tarutung for the 2023/2024 learning year totaling 125 people and a sample of 62 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire of 34 items, namely 18 items for variable X and 16 items for variable Y. The results of data analysis showed that there was a positive and significant influence on the use of the Two Stay Two Stray (TS-TS) type cooperative learning model on the learning activity of PAK students of grade VIII SMP Negeri 4 Tarutung Learning Year 2023/2024: 1) Test analysis requirements: a) positive relationship test obtained rxy value = 0.624 > rtable(a=0,05,n=62) = 0,254. b) Test the relationship of significant obtained tcount values > ttabel(a=0,05,dk=n-2=60)= 2,000. 2) Test the influence: a) Test the regression equation, obtained regression equation. b) Regression coefficient of determination test (r2) = 38,9%. 3) Test the hypothesis using the F test obtained Fcalculate > Ftable=(a=0.05,dk numerator k=20,dk denominator=n-2=62-2=60) which is 38.16 > 1.39. Thus, Ha is accepted and H0 is rejected.